Online taxi users' optimistic bias: China youths' digital travel and information privacy protection - Meng, Xiaoyang; Feng, Bobo (Frontiers in Psychology, 2022)
Digital travel platforms not only provided hailers with convenient travel, but also raised a series of problems regarding information privacy protection. In order to analyze privacy protection behavior, this study surveyed 441 subjects aged 18-35 who utilized digital travel platforms, based on a structural model of protective motivation theory. The results indicated that perceived threat, self-efficacy, and response efficacy had a positive and significant impact on youths privacy concern. Furthermore, privacy concern was positively related to privacy protection behavior, and was an intermediate variable between the relationships among perceived threat, self-efficacy, response efficacy, and privacy protection behavior. This study identified the moderating effect of youths’ knowledge on platform privacy settings between the relationship of privacy concern and protection behavior. In addition, the results confirmed that optimistic bias did exist among talented high privacy knowledge youths in terms of practical level in privacy management. These unique findings are the exceptional contributions and innovation points of this study.